HOW DO BANKERS WORK DEVIANTLY IN THE CREDIT SECTOR? - Sawitri, Dewi Khrisna; Mashud, Mustain; Mardiyanta, Antun (Universitas Brawijaya, Indonesia, 2021)
This research is implemented in the banking sector. Knowledge about counterproductive behavior that emerged in banking activity is still limited. Bankers, human resources in the banking sector, deal a lot with customers in their day-to-day job activity by assessing the credit proposal of their bank customers. Qualified credit assessment is essential to determine the approval of bank credit. The failure to assess qualified debtors will result in bad credit in which debtors do not repay the credit they receive. To get qualified credit assessment, bankers follow the 5C Principles in assessing credit proposals. Counterproductive work behavior occurs when workers perform indifferently from what the rules and norms of a company have stated. Qualitative research with a phenomenology approach was conducted to determine how these deviances performed while bankers assessed their customers' credit loan proposals under the 5C Principles. Six bankers with different job positions were the subjects of this study and were interviewed to get in-depth information. This research reveals items of behaviors related to production deviances in each principle they assessed. Deviances are reported in each principle then categorized into production ones since these behaviors deal a lot with how they perform their job in the credit sector.